2017
DOI: 10.1186/s12961-017-0185-9
|View full text |Cite
|
Sign up to set email alerts
|

Research impact of systems-level long-term care research: a multiple case study

Abstract: BackgroundTraditional reporting of research outcomes and impacts, which tends to focus on research product publications and grant success, does not capture the value, some contributions, or the complexity of research projects. The purpose of this study was to understand the contributions of five systems-level research projects as they were unfolding at the Bruyère Centre for Learning, Research and Innovation (CLRI) in long-term care (LTC) in Ottawa, Ontario, Canada. The research questions were, (1) How are par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…49 There is evidence supporting researchere knowledge user partnerships to facilitate knowledge creation and use. 50 These partnerships ensure the development of strategies and tools relevant to the LTC context to meet the needs of intended users and settings, and serve to foster ownership for implementation and outcomes. Our partnerships with resident and family council, LTC organizations, and health professional associations have resulted in the development and promotion of tools to support their respective constituents; the development of tools "for them-by them" ensures appropriateness, relevance, and will likely promote use.…”
Section: Discussionmentioning
confidence: 99%
“…49 There is evidence supporting researchere knowledge user partnerships to facilitate knowledge creation and use. 50 These partnerships ensure the development of strategies and tools relevant to the LTC context to meet the needs of intended users and settings, and serve to foster ownership for implementation and outcomes. Our partnerships with resident and family council, LTC organizations, and health professional associations have resulted in the development and promotion of tools to support their respective constituents; the development of tools "for them-by them" ensures appropriateness, relevance, and will likely promote use.…”
Section: Discussionmentioning
confidence: 99%
“…New approaches to impact assessment have been published in HARPS , including a list of indicators developed in France for assessing the outcome of translational cancer research [ 80 ], an approach for assessing research in low-resource settings in the Pacific Islands [ 81 ], two new frameworks from Australia that combined previous approaches [ 82 , 83 ], and two new approaches from The Netherlands by Mostert et al [ 84 ] and by Kok and Schuit [ 85 ]. The latter’s contribution mapping approach to assessing the impact of health research is increasingly informing other studies, including in The Netherlands [ 86 ], Ghana [ 87 ] and Canada [ 88 ].…”
Section: Editorialmentioning
confidence: 99%
“…In a recent edition of this journal (EPP), Heyeres, Tsey, Yang, Yan, and Jiang, (2018) examined the types of impact and the factors that enable effective translation of research findings into impact. The 24 included studies reported a wide range of impacts including the economic value of research (Alene & Coulibaly, 2009;Walker, Ryan, & Kelley, 2010;Wooding, Hanney, Buxton, & Grant, 2005), measurable improvements in health (Johnston, Rootenberg, Katrak, Smith, & Elkins, 2006), changes in clinical or professional practice (Bodeau-Livinec, Simon, Montagnier-Petrissans, Joel, & Fery-Lemonnier, 2006;Caddell, Hatchette, & McGrath, 2010;Donovan, Butler, Butt, Jones, & Hanney, 2014;Greenhalgh & Fahy, 2015;Jones, 2015;Kelly, Kent, McMahon, Taylor, & Traynor, 2016;Milat et al, 2013;Orians, Abed, Drew, Rose, Cohen and Phelps, 2009;Raftery, Hanney, Green, & Buxton, 2009), improved quality of care (Caddell, Hatchette & McGrath, 2010;Wooding et al, 2005), organisational awareness raising (Milat et al, 2013), and improved knowledge and understanding of health issues (Home, 2008 andKothari, Peter, Donskov, &Luciani, 2017). Six studies reported making an impact on guidelines or institutional policies (Greenhalgh & Fahy, 2015;Home, 2008;Jarman & Bryan, 2015;Jones, 2015;Kelly et al 2016;Wooding et al, 2005), while one reported on educational curriculum changes (Orians et al, 2009).…”
Section: Introductionmentioning
confidence: 99%